2018
DOI: 10.1186/s12879-018-3543-5
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous endophthalmitis caused by a multidrug-resistant hypervirulent Klebsiella pneumoniae strain belonging to a novel single locus variant of ST23: first case report in China

Abstract: BackgroundEndogenous endophthalmitis caused by hypervirulent Klebsiella pneumoniae (HVKP) is an emerging infectious disease commonly with a devastating visual outcome. Most HVKP strains display a wild-type susceptibility profile to antibiotics. However, reports of antimicrobial-resistant HVKP have increased over time, which poses a serious therapeutic dilemma.Case presentationA 25-year-old man with a liver abscess and poorly controlled diabetes mellitus was admitted for endophthalmitis due to K. pneumoniae. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 26 publications
2
26
0
1
Order By: Relevance
“…The K1 serotype of K pneumoniae is the major serotype that induces deep abscesses. [4,11,12] Invasive infection caused by K pneumoniae is common in immunosuppressed patients, but it could also be observed in some immunocompetent patients. It was reported that prevalence of K pneumoniae in healthy adults was 75%, with a high prevalence (23%) of serotype K1 or K2 isolates in Taiwan.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The K1 serotype of K pneumoniae is the major serotype that induces deep abscesses. [4,11,12] Invasive infection caused by K pneumoniae is common in immunosuppressed patients, but it could also be observed in some immunocompetent patients. It was reported that prevalence of K pneumoniae in healthy adults was 75%, with a high prevalence (23%) of serotype K1 or K2 isolates in Taiwan.…”
Section: Discussionmentioning
confidence: 99%
“…Other manifestations include lumbar or cervical spondylitis and discitis, septic pulmonary emboli, lung abscesses, splenic abscesses, necrotizing fasciitis, neck abscesses, cerebral abscesses, purulent meningitis, otitis media, osteomyelitis, arthritis, prostate abscesses, pylephlebitis, and psoas muscle abscesses. [1012,1618] The outcome of some patients with K pneumoniae -induced endophthalmitis could be complete visual loss. [2,1012] Furthermore, severe K pneumoniae infection could result in death because of intracranial hypertension, cerebral hernia, and sepsis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In East Asia, however Gram-negative bacterial particularly Klebsiella pneumoniae (KP) is more common. 3 Arising trend of KP infection has been observed worldwide [ 6 ]. The visual prognosis of Klebsiella infections is poor.…”
Section: Introductionmentioning
confidence: 99%
“…1 Las endoftalmitis endógenas en niños son raras; constituyen entre el 0,1 % y el 4 % de las endoftalmitis. 2 Los tejidos que primero se ven afectados son la retina, la coroides y el cuerpo ciliar, ya que tienen un alto flujo sanguíneo. Además, pueden estar enmascaradas como una uveítis, una celulitis preseptal, glaucoma congénito, conjuntivitis o un retinoblastoma.…”
Section: Introductionunclassified